Desentralisasi, Basis Sosial dan Praktek Kekuasaan Elit Politik di Tingkat Lokal Pasca Penerapan Otonomi Daerah - Ruman, Yustinus Suhardi (Bina Nusantara University, 2011)
Decentralization basically is acknowledged would make development process at the local level runs democratic. Otherwise, democracy at the local level is not only determined by the existing of democracy institution at the local level (election, parties, non-governmental organization). Democracy at the local level is also determined by behaviour and power practices by local elites at the local level. This journal shows that power practices at the local level tend to corrupt, ollygarchy and full of intimidations. Political elites who participate in the local political contestation tend to have social basic from the new order and the local nobles.